Modeling And Analysis Of Constants For Various Double Stator Permanent Magnet Brushless DC Motor - Md Zuki, Nor Aishah (2018)
Double stator topology is recently used for various applications where power segmentation and reliability are the main key factors.Double Stator Permanent Magnet Brushless DC Motor (DSPM BLDC) has high torque density because it has two air gaps due to two permeances.Thus, the torque produced will be almost doubled as a single stator.Therefore many researchers interested to increase the torque density using double stator topology.However, most double stators used surface mount rotor structure. The problem with this structure is that it requires large air gap that could reduce percentage of achieving higher torque with low volume ratio at optimum level.In addition,application such as hybrid or electric vehicle requires fast response motor that capable to react as soon as possible.Thus,the motor must have higher time response with lower electrical time constant,Te and mechanical time constant,Tm.However,there are few literature reported about time response for double stator topology.Basically,most of the literature studies the time response for linear motor and servo motor due to their application for high precision positioning.The time response is relates to various constant parameters of the motor.The advantage of high torque density offered by the double stator is very likely to be implemented for another application in the future. Therefore, to overcome this problem,a new type of double stator permanent magnet motor with Slotted Rotor (DSPM-SR) is introduced and this thesis is the study of the constants for various types of DSPM BLDC motor through model analysis.The usage of the proposed DSPM-SR is to minimize the flux leakage,thus increasing the flux linkage.The proposed DSPM-SR also has the highest torque density among other double stator topology.The objective of this research is to model various types DSPM BLDC and investigate the values of torque,electromotive force (emf),inductance,resistance, flux density,electrical time constant,Te and also mechanical time constant,Tm.For the modeling,the Permeance Analysis Method (PAM) will be used to derive the analytical equations that indicate the presence of two time constants,which are Te and Tm.Finite Element Method (FEM),is used to simulate the real characteristics of various types of DSPM BLDC motor that consider the presence of values Te and Tm.The smaller the response, the better the performance for fast response application. The result shows that the proposed DSPM-SR has good performance such as highest back emf,highest torque and good time response.A prototype of DSPM-SR has been fabricated and measured.The percentage difference of Analytical-FEM for Te and Tm is 4.2 % and 9.1 %, respectively.As a conclusion,this thesis provides an overview of modeling and analysis of various constants that could affect the performance of the double stator topology.